Green digitalization in the electric power industry - Julia Turovets; Liliana Proskuryakova; Alena Starodubtseva; Vincenzo Bianco (Foresight and STI Governance)
The lasting global economic downturn caused by the COVID-19 pandemic allows decision-makers and societies to re-think the basis and drivers of economic growth, laying the foundation for sustainable development. The green economic recovery takes place with a leading role played by the energy industry. This paper focuses on the application and desired effects of green digital technologies in the electric power industry in ten countries — the largest electricity producers and consumers. The study is designed in the framework of the sectoral innovation systems concept. The research tasks were addressed, first, through horizon scanning (the analysis of research and analytical publications). Second, the green digitialization indicators for the electric power industry in the selected countries were identified with the use of statistical and other available reliable data and compared. Third, a comparative analysis of national strategic documents was performed, along with corporate tasks and indicators that reflect the digital transformation at micro level. As a result of the study, key trends and three models of green digitalization at the national level were identified, the prerequisites and potential social and economic effects of the application of these technologies in electric power industry were described.